A receptance method for partial quadratic pole assignment of asymmetric systems. (15th February 2022) - Chen, Meng; Xie, Huiqing
Abstract: A new receptance method is proposed for partial quadratic pole assignment problem (PQPAP) of asymmetric systems with multi-input. We use receptance matrices of symmetric parts of open-loop systems to express the solution of PQPAP. Then we derive the sensitivities of changed eigenvalues of close-loop system and give the measure of robustness. On these grounds, an algorithm for solving the robust and minimum norm PQPAP is put forward. Our method utilizes receptance matrices of symmetric parts of asymmetric systems and it is applicable to the systems with multi-input. Finally, numerical results are given to show the efficiency of our method. Highlights: Receptance method is proposed for partial quadratic pole assignment problem (PQPAP) of asymmetric system with multi-input. Our method only uses receptance matrix of symmetric part of asymmetric system. The close-loop eigenvalue sensitivities are derived and used to measure robustness. Robust PQPAP is solved by transforming it into an optimization problem.